PENERAPAN HUKUM ADAT TERHADAP TINDAK PIDANA PERAMBAHAN HUTAN DI KECAMATAN LANGGAM KABUPATEN PELALAWAN - Halimah Halimah; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
After abstracting of permit of Rights of Double Limited Liability Forest Enterpasing of Marta byForestry Minister of through Number decision 10258/Kpts-II/2002 date of 13 December 2002 jo Number282/Kpts-II/2003 date of 25 August 2003 as preparation of directing of area of conservation of Tesso Nilo,concurrently in society form the custom area which unilaterally acknowledge the custom forest in area ofNational Park of Tesso Nilo so that management and enableness of forest area shall no longger accordingto order of applicable law where arising of customary law but there are its execution deviation. Problem ofthis research is What Will Be Applying of Customary Law To Doing An Injustice of Forest Encroachment inSubdistrict of Langgam of Regency Pelalawan, to what extent existence customary law to ForestEncroachment in Subdistrict of Langgam of Regency Pelalawan and what becoming resistance and strive toovercome the resistance of Applying of Customary Law To Doing An Injustice of Forest Encroachment inSubdistrict of Langgam of Regency Pelalawan.This research represent the research sosiologis which have location in] Subdistrict of Langgam ofRegency Pelalawan. As for data source which is utilizing in this research is Primary Data, seconds Dataand Tertiary with the Technique Data Collecting use the Observation, Interview the non structure,questionnaire And Bibliography Study.Pursuant to research indicate that the applying of customary law to doing an injustice of ForestEncroachment in Subdistrict of Langgam of Regency Pelalawan is not maximal conducted to activity societyanticipated do the Forest Encroachment in custom forest. Existence customary law to Forest Encroachmentin Subdistrict of Langgam of Regency Pelalawan in the form of order concerning collision form and alsocustom sanction but is not effective executed because until present moment of Forest Encroachment still behappened. Resistance of Applying customary law to doing an injustice of Forest Encroachment inSubdistrict of Langgam of Regency Pelalawan there is two factor, namely factor of society of custom andfactor outside custom society. Strive to overcome the resistance of applying customary law to doing aninjustice of Forest Encroachment in Subdistrict of Langgam of Regency Pelalawan is conduct the evaluationby totally to area of custom forest, data and also assess the performance there, while to the transfer of areafunction hence all custom society by together take care of and commit to remain to to take care of andpreserve the area of custom forest.Keyword : Customary Law, Criminal Act, Forest Encroachment